AKTIVITAS PENYULUHAN PERTANIAN PADA OTONOMI DAERAH DI KECAMATAN TUGUMULYO KABUPATEN MUSI RAWAS - Winanto, Agus; Abubakar, Rafeah (Societa: Jurnal Ilmu-Ilmu Agribisnis, 2019)
ABSTRACT This study aims to determine the Agricultural Extension Activities in Regional Autonomy And The Benefits Of Agricultural Extension Activities For Farmers In Tugumulyo District, Musi Rawas District. This research was carried out in the Tugumulyo sub-district, Musi Rawas regency in May 2019 until July 2019. The research method used was a case study. The sampling method used was purposive sampling and random sampling methods. The data collection methods used in this study are in-depth interviews with respondents who have been determined using questioner tools that have been prepared previously. Data processing and analysis is done using descriptive-qualitative methods. The results of the study showed that the implementation of the extension program in 2018 in the subdistrict of Tugumulyo had run well and smoothly and the implementation of agricultural extension conducted by agricultural extension workers was in accordance with existing guidelines. And the benefits that can be obtained by farmers from the extension activities are increasing knowledge for farmers, being able to control pests correctly, getting assistance in the form of Saprodi and Alsintan and increasing production and the level of technology adoption that is getting better.